Study on Ovitrap Surveillance and Molecular Phylogeny of Dengue Vectors (Aedes aegypti and Aedes albopictus) based on Cytochrome C Oxidase Subunit I (COI) Genes from Different Habitat Types of North Eastern, India - Borah, Himadri; Bora, Dipsikha (Asian Journal of Biological and Life Sciences)
Background: Larval surveillance plays crucial role in monitoring dengue vector surveillance. Conventional vector indices are failed in monitoring vector abundance and risk of transmission. ovitrap surveillance and molecular phylogeny study was conducted. Materials and Methods: Ovitrap surveillance was carried using different ovitrap indices which correlate with environmental parameters. Phylogeny study was carried out using mtCOI genes as morphological characterization of mosquitoes lacks accuracy to characterized closely related species. Results: Findings revealed that Aedes albopictus was dominant over Aedes aegypti in ovitrap placement locations. And temperature, rainfall and habitat types serve as major factors contributing to variations in ovitrap indices. Molecular phylogeny revealed that the isolates form distinct grouped into separate clusters which indicate polymorphisms in gene among the isolates and signify sequence diversity of mt COI genes in Aedes mosquito species differs geographically which further differentiate a population and brings new identity. Conclusion: The study helps in measuring the population status of dengue vector abundance, forecasting dengue outbreaks and served as a powerful indicator to adopt different control measures.
Keywords: Aedes aegypti; Aedes albopictus; Polymorphisms; Population